Isolation of a novel herpesvirus from a Pacific white-sided dolphin - Noguchi, Keita; Shimoda, Hiroshi; Terada, Yutaka; Shimojima, Masayuki; Kohyama, Kaoru; Inoshima, Yasuo; Maeda, Ken (Archives of virology, 2013)
During establishment of primary cell culture from the kidney of a dead Pacific white-sided dolphin ( Lagenorhynchus obliquidens ), a cytopathic effect was observed. Polymerase chain reaction with a set of herpesvirus consensus primers yielded a fragment of the expected size. Nucleotide sequencing of the product indicated that the isolated virus was closely related to an alphaherpesvirus detected in a bottlenose dolphin in the United States, but the sequence identity at the protein level was low (86.6 %). Phylogenetic analysis of the encoded sequence confirmed that the new isolate belonged to the subfamily Alphaherpesvirinae and clustered together with other cetacean alphaherpesviruses. The complete gene encoding glycoprotein B (2,757 bp) was amplified from the novel isolate; the encoded protein was compared with the corresponding protein of other herpesviruses, revealing that this virus belongs to the genus Varicellovirus . Taken together, these results suggest that this virus corresponds to a novel herpesvirus capable of infecting Pacific white-sided dolphins.